2012
DOI: 10.1521/psyc.2012.75.4.355
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Level of Personality Organization on Treatment Response: A Systematic Review

Abstract: This paper provides a systematic review of extant research concerning the association between level of personality organization (PO) and psychotherapy response. Psychotherapy studies that reported a quantifiable association between level of PO and treatment outcome were examined for eligibility. Based on stringent inclusion and exclusion criteria, we identified 18 studies from 13 original data sources. Participants in these studies had a variety of mental disorders, of which mood, anxiety, and personality diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 80 publications
5
47
0
3
Order By: Relevance
“…This position was recently empirically supported by the review conducted by Koelen et al (2012). We found also that expert practitioners of various theoretical orientations (most of whom were not psychodynamically oriented) felt that personality organization is a very important dimension in understanding their patients, and that personality patterns express themselves across the range of personality structure.…”
Section: The Psychodiagnostic Chart (Pdc)supporting
confidence: 55%
“…This position was recently empirically supported by the review conducted by Koelen et al (2012). We found also that expert practitioners of various theoretical orientations (most of whom were not psychodynamically oriented) felt that personality organization is a very important dimension in understanding their patients, and that personality patterns express themselves across the range of personality structure.…”
Section: The Psychodiagnostic Chart (Pdc)supporting
confidence: 55%
“…However, the level of personality organization may be the most parsimonious and important factor in considering the response to and type of treatment (Koelen et al, 2012;McWilliams, 2011). Koelen et al (2012) identified 18 studies that suggest that higher initial levels of personality organization are moderately to strongly associated with better treatment outcome. Moreover, the authors found that patients with higher initial levels of personality organization may do better with interpretive versus supportive interventions in predicting treatment outcome.…”
mentioning
confidence: 99%
“…Further research is also needed on the patient characteristics that may predict and modify change in personality functioning, and comparison between different outcome domains in short-vs. long-term therapy, in order to define the patient groups particularly in need of long-term therapy. The limited research, based on other outcome dimensions, suggests that the assessment of psychological suitability can be used to improve the fit between the patient and treatment duration (Laaksonen et al, 2013;Lindfors et al, 2014) as well as between the patient and the form of intervention needed (Koelen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%